2022
DOI: 10.1097/hjh.0000000000003129
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia regulates fibrosis-related genes via histone lactylation in the placentas of patients with preeclampsia

Abstract: Background: Histone lactylation, a novel epigenetic modification induced by hypoxia and lactate, plays an important role in regulating gene expression. However, the role of histone lactylation in the pathogenesis of preeclampsia remains unknown.Methods: Placentas from preeclamptic patients and control pregnant women were collected for protein immunoassay to detect the expression level of histone lactylation, and two trophoblast cell lines were used to simulate the effect of histone lactylation on genes.Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…qRT-PCR was conducted to confirm this result. Histone lactylation modifications usually regulate the process of glycolysis or inflammation through gene transcription [ 45 ]. ChIP-seq and CUT&Tag assays were employed to ascertain the binding affinity of lactate modification towards relevant genes [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…qRT-PCR was conducted to confirm this result. Histone lactylation modifications usually regulate the process of glycolysis or inflammation through gene transcription [ 45 ]. ChIP-seq and CUT&Tag assays were employed to ascertain the binding affinity of lactate modification towards relevant genes [ 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…We read with great interest the article by Li et al [1]. In the article, the authors confirmed several fibrosis-related genes induced by hypoxia in trophoblastic cells and identified elevated levels of histone lactylation in preeclampsia placenta, which provides a new view of placental dysfunction in preeclampsia at the level of posttranslational lactylation modification.…”
mentioning
confidence: 84%
“…There is compelling evidence that the upregulation of glycolysis in trophoblast cells, macrophages, and myocardial endothelial cells contributes to the progression of placental, pulmonary, and myocardial fibrosis, respectively [88][89][90]. Reduced blood flow to the uteroplacental unit in preeclampsia leads to a hypoxic condition in the placenta, which in turn promotes excessive lactate production by trophoblast cells and induces histone lactylation to regulate the expression of genes associated with preeclamptic placental fibrosis (FN1 and SERPINE1) [88].…”
Section: Fibrosismentioning
confidence: 99%